Exploring experiences of HIV care to optimize patient-centred care in Conakry, Guinea: a qualitative study - Kolié, Delphin; Guillard, Etienne; Sow, Abdoulaye; Manet, Hawa; Camara, Bienvenu Salim; Bigirimana, Théophile; Harouna, Mamane; Delamou, Alexandre (Frontiers in Reproductive Health, 2024)
Introduction Studies on the organisation of care and the power dynamic between providers and patients with HIV in sub-Saharan Africa are rare. This study aims to describe the patient-provider relationship and explore the challenges to optimal and patient-centred care for HIV patients. Methods This was a qualitative exploratory descriptive study using in-depth individual interviews and focus group discussions. In total, 17 individual interviews and 5 focus group discussions were conducted. This was conducted in four urban health facilities in Conakry, the capital of Guinea. Three group of participants were included in this study namely patients with HIV; health providers including facilities and services managers; and psychosocial counsellors. Psychosocial counsellors provide emotional and psychosocial support to HIV patients. Their role in the organization care in Guinea is new and they contribute to strengthening adherence of patients with HIV to ARV treatment. Results Patients with HIV, health providers, and psychosocial counsellors have a positive perception of the patient-provider relationship. This relationship was characterized essentially by maintaining confidentiality of HIV status disclosure, caring attitudes towards patients (being available, adjusting locations for accessing ART, based on patients’ preferences), and participating in HIV patient’s social life. However, scolding and miscommunication about the interpretation of viral load tests were reported. The shortage of human resources, low salaries of health staff, poor infrastructure, and the financial burden borne by patients with HIV impede the implementation of optimal patient-centred care. Conclusion Integrating psychosocial counsellors in HIV care organization, improving access to ARV, infrastructure, increasing human resources, and removing the financial burden for HIV patients are needed to optimal patient-centred care in Guinea.